Energy production system optimization: Evidence from Pakistan. (February 2018) - Zameer, Hashim; Wang, Ying
Abstract: The ongoing energy crisis in Pakistan and the dependency on thermal electricity generation has contributed to the necessity to optimize energy production system. The expensive thermal electricity and inability to recover its cost gives unprecedented rise to the electricity tariffs. In this study, optimization of the energy production system has been performed using linear programing model. As the high cost of electricity generation has been found as the root cause of energy crises, the objective function of the proposed model is cost minimization that will also reduce the circular debt. Specifically, it has examined the optimum proportion of energy production from each available source under two different scenarios. The first scenario considers that the existing system should be used at its maximum capacity; in the second scenario, seventy percent utilization of power plants has been examined. The second scenario summarizes the optimum mix of energy production which minimizes the cost of electricity production. The differential cost that is payable by the government as a subsidy is also compensated. Similarly, it reduces circular debt that is a bottleneck between power generation companies and oil supply companies. Thus, the proposed model has a tendency to minimize the cost of energy production, and further reduce circular debt as well as the burden of a subsidy on the government. The study specifies the problems confronting Pakistan's energy sector and identifies the key elements of a potential policy response to address the country's severe power crisis.